What should banks do? A Minskyan analysis - L. Randall Wray (Levy Economics Institute of Bard College, 2010)
In this new brief, Senior Scholar L. Randall Wray examines the later works of Hyman P. Minsky, with a focus on Minsky's general approach to financial institutions and policy. The New Deal reforms of the 1930s strengthened the financial system by separating investment banks from commercial banks and putting in place government guarantees such as deposit insurance. But the system's relative stability, and relatively high rate of economic growth, encouraged innovations that subverted those constraints over time. Financial wealth (and private debt) grew on trend, producing immense sums of money under professional management: we had entered what Minsky, in the early 1990s, labeled the money manager phase of capitalism. With help from the government, power was consolidated in a handful of huge firms that provided the four main financial services: commercial banking, payments services, investment banking, and mortgages. Brokers didn't have a fiduciary responsibility to act in their clients' best interests, while financial institutions bet against households, firms, and governments. By the early 2000s, says Wray, banking had strayed far from the (Minskyan) notion that it should promote the capital development of the economy.
Keywords: 330; Bank; Finanzsektor; Bankensystem; Kapitalismus; Bankenpolitik; Bankenreform